The effect of managerial overconfidence on investment - Dashtbayaz, Mahmoud Lari; Mohammadi, Shaban (International Journal of Accounting and Economics Studies, 2016)
Overconfidence or experience-based learning theory in behavioral finance is a subsidiary of confidence. One of the most detrimental behavioral biases in the field of behavioral finance is that investors will manifest as a lack of understanding of the risk of capital loss, the transaction or the transaction repeatedly to find a hot stock and widely traded futures and having a non-diversified portfolio, all serious risks for the enterprise you are looking for. One of the implications of each common biases of overconfidence, lack of foresight is real. Therefore, it is necessary to protect investors against overconfidence and financial advisors to help them in this regard. Overconfidence leads investors to predict their skills over estimate and find the belief that they cannot market timing. Detection and mitigation of confidence too, is a fundamental step in designing the foundations of a good financial plan. Too much trust in their own people, the strongest findings in the psychology of judgment. In this paper, the risks of overconfidence management and examine its impact on investor portfolios. The effect of managerial overconfidence on investment